Nutrition essentials for nursing practice - Dudek, Susan G. (Philadelphia, PA: Wolters Kluwer, 2022)
"Preface Like air and sleep, nutrition is a basic human need essential for survival. From curing hunger to reducing the risk of chronic disease, nutrition is ever changing in response to technological advances and cultural shifts. Because nutrition at its most basic level is food-for the mind, body, and soul-it is a complex blend of science and art. Although considered the realm of the dietitian, nutrition is a vital and integral component of nursing care across the life cycle and along the wellness-illness continuum. By virtue of their close contact with clients and families, nurses are often on the front line in facilitating nutrition. Nutrition is woven into all steps of the nursing care process, from assessment and nursing analysis to implementation and evaluation. This textbook seeks to give student nurses an essential nutrition foundation to better serve themselves and their clients"--
"Nutrition Essentials for Nursing Practice, 9th Edition gives nursing students the understanding of nutrition theory and application to ensure effective client care across the life cycle and the health-illness continuum. Incorporating nutrition throughout the nursing care process, Susan Dudek's concise yet thorough text equips tomorrow's nurses with the latest evidence-based practices and recommendations to facilitate nutrition on the front lines of nursing practice, from assessment and nursing diagnoses to implementation and evaluation. The most up-to-date resource of its kind, this revised edition includes the Dietary Guidelines for Americans, 2020-2025 and makes need-to-know information more accessible than ever with a student-friendly format, improved organization, engaging case studies, and adaptable content optimized for use in standalone courses, online, or a fully integrated curriculum. Ensure a mastery of essential nursing skills and equip students for success throughout the nursing education continuum with the complete Nutrition Essentials for Nursing Practice, 9th Edition solution: Nutrition Essentials for Nursing Practice, 9th EditionLippincott® CoursePoint for Nutrition Essentials for Nursing Practice, 9th Edition"--
Machine generated contents note: Unit 1: Nutrition Fundamentals -- Chapter 1 Nutrition in Health -- Chapter 2 Guidelines for Healthy Eating -- Chapter 3 Carbohydrates -- Chapter 4 Protein -- Chapter 5 Lipids -- Chapter 6 Vitamins -- Chapter 7 Water and Minerals -- Chapter 8 Energy Balance -- -- Unit 2: Nutrition in Health Promotion -- Chapter 9 Food and Supplement Labeling -- Chapter 10 Consumer Interests and Issues of Food Access -- Chapter 11 Cultural and Religious Influences on Food and Nutrition -- Chapter 12 Healthy Eating for Healthy Babies -- Chapter 13 Nutrition for Infants, Children, and Adolescents -- Chapter 14 Nutrition for Older Adults -- -- Unit 3: Nutrition in Clinical Practice -- Chapter 15 Hospital Nutrition: Defining Nutrition Risk and Feeding Clients -- Chapter 16 Enteral and parenteral nutrition -- Chapter 17 Nutrition for Obesity and Eating Disorders -- Chapter 18 Nutrition for Clients with Critical Illness -- Chapter 19 Nutrition for Clients with Upper Gastrointestinal Disorders -- Chapter 20 Nutrition for Patients with Disorders of the Lower GI Tract and Accessory Organs -- Chapter 21 Nutrition for Patients with Diabetes Mellitus -- Chapter 22 Nutrition for Patients with Cardiovascular Disorders -- Chapter 23 Nutrition for Patients with Kidney Disorders -- Chapter 24 Nutrition for Patients with Cancer or HIV/AIDS -- Appendices A-D & other BM -- .
Includes bibliographical references and index.
Keywords: Diet therapy; Nutrition; Nursing; MEDICAL / Nursing / Nutrition